A fully packed water-proof, humidity resistant triboelectric nanogenerator for transmitting Morse code. (June 2019) - Chandrasekhar, Arunkumar; Vivekananthan, Venkateswaran; Khandelwal, Gaurav; Kim, Sang Jae
Abstract: Triboelectric nanogenerators (TENG) are widely reported for harnessing and utilization of waste energy. The external influence such as relative humidity is well informed to influence the output performance of TENG which makes it unsuitable for various applications. Herein, we demonstrated a full packed waterproof WP-TENG in a vertical contact-separation mode using PDMS and nickel foam as tribo-active material. The obtained output voltage and short-circuit current was 88 V and 6.2 μA with a maximum power of ≈350 μW and a power density of ≈4 mW/m 2 . The waterproof nature was confirmed by soaking WP-TENG in water for different time intervals. The influence of relative humidity on the output of TENG was also tested. The stability of the device output in water and high relative humidity makes it suitable for various real-time applications. Finally, we reported a novel concept of sending the Morse code using WP-TENG. The alphabet and numeric are encoded as per international Morse code. The real time applicability was proved by sending a message "Jeju National University Help Me" over a long distance. Next, as a visual demonstration, a LED circuit was connected with the WP-TENG, and "SOS" code was generated. According to the Morse code the LED was glowing in different intensity. We believe that this concept opens a new domain of TENG in communication applications. Graphical abstract: The graphical Abstract describes the fabrication of a fully packed WP-TENG and demonstrated its electrical output performance under various percentages of relative humidity as well as under different time duration of soaking in water. Further the device demonstrates its capability in transmission of Morse code as well the same concept demonstrates the LED lit up showing SOS signaling.Image 1 Highlights: In this present work, we have provided a solution by introducing a fully-packed water-proof TENG which can harvest the mechanical energy with a stable efficiency irrespective to the humidity conditions. The fully packed TENG works on contact-separation mode and packed with a flexible PET and laminated on its ends. The device is extremely lightweight (1.9 g) and generates a maximum power of 350 μW. The electrical output of TENG device was tested under different soaking (placing in water) time and measured under various percentages of relative humidity and at both the testing conditions the electrical output is stable without any interruptions. Further, the device was used to demonstrate an application of Morse code transmission and received a message "Jeju National University" and "Help Me". To visually demonstrate the Morse code generation a single LED was directly connected to the WP-TENG, and we generated a message "S O S" by pressing the WP-TENG.